1999
DOI: 10.1042/cs0970283
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of clinical doses of cyclosporin A on erythrocyte Na+/K+-ATPase activity

Abstract: Cyclosporin A (CsA) may exert its cytotoxic effects by altering the activity of different plasma membrane transport systems. Although CsA may act at the gene level, it has been also suggested that it can directly alter transport processes at the plasma membrane. To examine this possibility in a physiological context, we determined Na(+)/K(+)-ATPase activity in erythrocytes from two groups of subjects receiving CsA treatment: group I consisted of kidney transplant patients, and group II comprised patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…171,172 In addition, receptor targets for cyclosporin have been identified in human cells of lymphoid and fibroblast origin using cyclosporin-diazirine. 173 Other studies with the diazirine analogue have demonstrated cyclosporin is not responsible for inhibition of Na,K-ATPase, 174 whilst it does inhibit P-glycoprotein, [175][176][177] its inability to bind to mutant P-glycoprotein has also been reported. 178 Volke et al have developed several PAL probes that accommodate a photoreactive diazirine, an indicator unit (biotin) and a bioactive ligand, all bound to a central scaffold.…”
Section: Miscellaneous Diazirine Analogues For Palmentioning
confidence: 99%
“…171,172 In addition, receptor targets for cyclosporin have been identified in human cells of lymphoid and fibroblast origin using cyclosporin-diazirine. 173 Other studies with the diazirine analogue have demonstrated cyclosporin is not responsible for inhibition of Na,K-ATPase, 174 whilst it does inhibit P-glycoprotein, [175][176][177] its inability to bind to mutant P-glycoprotein has also been reported. 178 Volke et al have developed several PAL probes that accommodate a photoreactive diazirine, an indicator unit (biotin) and a bioactive ligand, all bound to a central scaffold.…”
Section: Miscellaneous Diazirine Analogues For Palmentioning
confidence: 99%